PSYCHOLOGICAL WELL-BEING TREATMENT TERHADAP MEANING IN LIFE REMAJA YANG BERPOTENSI JUVENILE DELINQUENT - Citra Widyastuti; Nurul Hartini (UIN Sunan Kalijaga Yogyakarta, 2024)
Juvenile delinquent behavior is carried out by someone in the age range of less than 18 years. To have good resilience, adolescents need to have psychological well-being. Psychological well-being is a description of psychological functioning well and positively. The ability of individuals to make decisions and set their behavior is related and related to the ability of individuals to make meaning of their lives. This study aims to determine the relationship between juvenile delinquent behavior, meaning in life, and psychological well being. This research method uses quantitative and qualitative approaches. The quantitative approach uses a true experimental design with the pretest-posttest control group design model. The qualitative approach uses a descriptive qualitative design to see changes in the behavior of each research subject. In this study, the authors used non-parametric analysis techniques in the form of the Wilcoxon signed ranks test. Based on the results of the wilcoxon test analysis above, it states that psychological well-being has no significant effect on meaning in life. This can be seen from the significance result of 0.219> 0.01. The conclusion in this study is that psychological well-being treatment has no significant effect on meaning in life in adolescents who are potentially juvenile delinquent. There is a difference between meaning in life in adolescents who have the potential to be juvenile delinquent after being given psychological well-being treatment. Keywords: Psychological Well-Being, Meaning In Life, Juvenile Delinquent.